Generalized Nekrasov Matrices and Applications (Journal of Computational Mathematics, 2003)
In this paper, the concept of generalized Nekrasov matrices is introduced, some properties of these matrices are discussed, obtained equivalent representation of generalized diagonally dominant matrices.
Keywords: Nekrasov matrix; Generalized Nekrasov matrix; Generalized diagonally dominant matrix.